2022
DOI: 10.3390/molecules27238629
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the Antioxidant Activity, Polyphenolic Content, and Characterization of Selected Himalayan Herbs: Anti-Proliferative Potential in HepG2 Cells

Abstract: Natural antioxidants derived from plants have played a vital role in preventing a wide range of human chronic conditions and provide novel bioactive leads for investigators in pharmacotherapy discovery. This work was designed to examine the ethnopharmacological role of Urtica dioica (UD), Capsella bursa-pastoris (CBP), and Inula racemosa (IR). The total phenolic and flavonoid contents (TPC and TFC) were illustrated through colorimetric assays, while the antioxidant activity was investigated through DPPH and AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Based on the findings obtained in the first stage of CS bioactive compounds extraction optimization, it can be seen that the aqueous CS extracts were characterized by significantly lower antioxidant activity and the TPC compared to methanol and ethanol extracts. A similar trend was demonstrated in the works of Bhatt and Parajuli [59] and Yousuf et al [60], in which alcoholic extracts showed a greater antioxidant activity and TPC compared to other extracts. For this reason, the possibility of using water as an extractant was excluded from further experimental extraction.…”
Section: Selection Of the Crucial Operational Extraction Process Vari...supporting
confidence: 87%
“…Based on the findings obtained in the first stage of CS bioactive compounds extraction optimization, it can be seen that the aqueous CS extracts were characterized by significantly lower antioxidant activity and the TPC compared to methanol and ethanol extracts. A similar trend was demonstrated in the works of Bhatt and Parajuli [59] and Yousuf et al [60], in which alcoholic extracts showed a greater antioxidant activity and TPC compared to other extracts. For this reason, the possibility of using water as an extractant was excluded from further experimental extraction.…”
Section: Selection Of the Crucial Operational Extraction Process Vari...supporting
confidence: 87%
“…amethystine , which was 850 µg/mL for stems and 2000 µg/mL for leaves. Many studies showed a significant positive correlation between the phenolic compounds contained in herbal extracts [ 62 ] or other plant components, such as lignin, and their antioxidant activity [ 63 , 64 ]. However, in this study, the levels of polyphenolic compounds in the leaves and stems did not exhibit significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the surface properties of NPs, such as being hydrophobic, hydrophilic, lipophilic, or lipophobic, are determined by their surface characteristics. These properties significantly influence how NPs interact with biological systems, including their solubility, stability, and ability to interact with cell membranes, impacting their biomedical applications and effectiveness [ 62 ]. In the study published by Motelica et al [ 81 ], the shape of the NPs was influenced by the solvent used in their synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Plant material was dried, crushed into fine powder utilizing a grinder and then sieved to obtain the desired particle size. A 10% plant fraction was made by steeping 5 g (±0.05) of plant powder in deionized water (50 mL) for 15 min at 95–100 °C [ 25 ]. The plant fractions were then filtered using Whatman No.…”
Section: Methodsmentioning
confidence: 99%